2014
DOI: 10.1002/ijc.29200
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of functional domains in the Merkel cell polyoma virus Large T antigen

Abstract: Merkel cell polyomavirus (MCPyV)-positive Merkel cell carcinoma (MCC) tumor cell growth is dependent on the expression of a viral Large T antigen (LT) with an intact retinoblastoma protein (RB)-binding site. This RB-binding domain in MCPyV-LT is-in contrast to other polyomavirus LTs (e.g., SV40)-embedded between two large MCPyV unique regions (MUR1 and MUR2). To identify elements of the MCPyV-LT necessary for tumor cell growth, we analyzed the rescue activity of LT variants following knockdown of the endogenou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
53
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 48 publications
(53 citation statements)
references
References 45 publications
0
53
0
Order By: Relevance
“…The only exception was the cell line LoKe for which no RB1 expression could be detected. Notably, LoKe, although encoding a functional truncated MCPyV-LT [20], is up to date the only MCPyV-positive MCC cell line tested which is not dependent on LT expression for cell growth [21]. Immunoblot analysis confirmed the expression of all PPs in all other cell lines as well as the lack of RB1 expression in LoKe (Figure 1b).…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…The only exception was the cell line LoKe for which no RB1 expression could be detected. Notably, LoKe, although encoding a functional truncated MCPyV-LT [20], is up to date the only MCPyV-positive MCC cell line tested which is not dependent on LT expression for cell growth [21]. Immunoblot analysis confirmed the expression of all PPs in all other cell lines as well as the lack of RB1 expression in LoKe (Figure 1b).…”
Section: Resultsmentioning
confidence: 95%
“…First, the TA shRNA induced growth arrest can be rescued to the same extent by an LT cDNA as by a TA gene (coding for sT and LT) indicating that with this experimental system we evaluate only LT functions although the applied TA shRNA also targets sT [20, 22]. Second, in the cell line WaGa the rescue by TA or LT is incomplete demonstrating a similar rescue activity as achieved by RB1 knockdown (Figure 2; [20, 22]). Hence, it is likely that the TA shRNA exerts growth inhibiting off-target effects in WaGa.…”
Section: Resultsmentioning
confidence: 99%
“…The short NLS of MCV LT that lies between these two regions (277–280 aa) was initially believed to also be conserved in tumors [29], but recent evidence indicates that the NLS is not preferentially preserved in MCC [44,47]. In the cases where the NLS is eliminated by tumorspecific mutations to LT (as in cell lines MCC350, MCCL-11, and MCCL-12) nuclear localization is not lost, but rather both nuclear and cytoplasmic distribution are observed [44].…”
Section: Large T Antigenmentioning
confidence: 99%
“…A recent study aiming at the identification of the cellular interaction partner(s) for the PP-binding domain of LT identified the three PP family members RB1, p107 and p130 as the main candidates. Knockdown of these individually demonstrated that knockdown of RB1 alone was sufficient to rescue the effect of LT knockdown-mediated cellular growth impairment [44] (Fig. 1).…”
Section: Introductionmentioning
confidence: 99%